2013
DOI: 10.1002/oby.20454
|View full text |Cite
|
Sign up to set email alerts
|

Acylated ghrelin limits fat accumulation and improves redox state and inflammation markers in the liver of high‐fat‐fed rats

Abstract: Objective: Obesity commonly causes hepatic lipid accumulation that may favor oxidative stress and inflammation with negative clinical impact. Acylated ghrelin (A-Ghr) modulates body lipid distribution and metabolism, and it may exert antioxidant effects in vitro as well as systemic anti-inflammatory effects in vivo. The impact of A-Ghr on liver triglyceride content, redox state and inflammation markers in dietinduced obesity was investigated. Design and Methods: A-Ghr (200-lg=injection: HFG) or saline (HF) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…Furthermore, the effect of AMPK activation is stimulation of hepatic fatty acid oxidation and ketogenesis, inhibition of cholesterol synthesis, lipogenesis, and triglyceride synthesis [30], exerting an therapeutic effect on NAFLD. Ghrelin increases food intake and activates the AMPK signaling pathway [14,20,31]. Consistently, our study found that phosphorylation level of AMPK was reduced in the NAFLD group but restored by ghrelin without disturbing total AMPK.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, the effect of AMPK activation is stimulation of hepatic fatty acid oxidation and ketogenesis, inhibition of cholesterol synthesis, lipogenesis, and triglyceride synthesis [30], exerting an therapeutic effect on NAFLD. Ghrelin increases food intake and activates the AMPK signaling pathway [14,20,31]. Consistently, our study found that phosphorylation level of AMPK was reduced in the NAFLD group but restored by ghrelin without disturbing total AMPK.…”
Section: Discussionsupporting
confidence: 76%
“…Likewise, another study has reported that high levels of ghrelin are associated with low risk of developing fatty liver [23]. The most recent study has confirmed our belief that ghrelin could have a therapeutic effect in NAFLD [20]. However, the therapeutic mechanism of ghrelin in NAFLD remains largely unknown, especially the way to reduce lipid accumulation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore it is likely that this elevation of ghrelin is an attempt to suppress inflammation, as ghrelin has strong anti-inflammatory actions by inhibiting proinflammatory cytokines, augmenting anti-inflammatory cytokines [65,66] and reducing hypothalamic glial activation [67]. Furthermore, administration of ghrelin showed to be beneficial in fasting or high-fat diet induced inflammation [68,69].…”
Section: Hypothalamic Inflammation: Orexigenic Signallingmentioning
confidence: 96%
“…Ghrelin administration has shown protective activity in rodent models of non-alcoholic fatty liver disease, liver damage induced by carbon tetrahydrochloride or acetaminophen, and hepatic ischemia-reperfusion [106][107][108][109][110]. Since TNF-alpha is a key mediator of hepatic inflammation in many syndromes, ghrelin-mediated suppression of this cytokines seems likely to play a role in these benefits.…”
Section: Ghrelin Suppresses Inflammation and Autoimmunitymentioning
confidence: 99%